Micro and Nanomanufacturing Volume II (Springer International Publishing, 2018)
This book is a comprehensive treatment of micro and nanofabrication techniques, and applies established and research laboratory manufacturing techniques to a wide variety of materials. It is a companion volume to "Micro and Nanomanufacturing" (2007) and covers new topics such as aligned nanowire growth, molecular dynamics simulation of nanomaterials, atomic force microscopy for microbial cell surfaces, 3D printing of pharmaceuticals, microvascular coaptation methods, and more. The chapters also cover a wide variety of applications in areas such as surgery, auto components, living cell detection, dentistry, nanoparticles in medicine, and aerospace components. This is an ideal text for professionals working in the field, and for graduate students in micro and nanomanufacturing courses.